Association between dental caries in mothers and their children under 72 months old from the Center of Growth and Development- Breastfeeding Hospital Nacional Cayetano Heredia, Lima -Peru. - Falcon Aguilar, Milagros (2021)
Objective: Analyze the association between dental caries in mothers y and their children under 72 months old from the Center of Growth and Development- Breastfeeding in the Hospital Nacional Cayetano Heredia in Lima, Peru. Material and methods: This study was analytical, observational and cross- sectional. The analysis was made with a sample of 204 subjects, 102 pairs of mothers-children, the children were under 72 months old. Oral examinations were performed to the mothers and their children, we tried to associate the prevalence of dental caries and dental caries experience with other variables such as age, sex and level of education. Chi- Square corrected by Yates and Fisher was used as a statistical test. The study had a 95% of confidence level and p<0.05. Results: The prevalence of dental caries in mothers was 59.8% and in their children 9.8%. The mothers had an average of 6.8 DMFT and DMFS of 16.7 in dental caries. The children had an average of 0.3 ceod with the same value for the ceos. Conclusions: There was no association between dental caries in mothers and their children under 72 months of the Growth and Development Center - Breastfeeding in the Hospital Nacional Cayetano Heredia, Lima- Peru.